On the interplay between electromigration and electroosmosis during electrokinetic transport in heterogeneous porous media. (15th April 2022) - Sprocati, Riccardo; Rolle, Massimo
Highlights: Electrokinetic transport investigated in multidimensional heterogeneous experiments. Proof of complex interplay between advection, electroosmosis and electromigration. Heterogeneity and pore water chemistry strongly impact tracer transport by EK. Different patterns of reactants' mixing and enhanced contaminant removal during EK. Process-based modeling illuminates EK transport behavior in heterogeneous media. Abstract: Electrokinetic techniques represent a valuable approach to enhance solute transport, reactant delivery and contaminant degradation in complex environmental matrices, such as contaminated soil and groundwater, and have a great potential for the remediation of many organic and inorganic pollutants. This study investigates the complex interplay between the key electrokinetic transport mechanisms, electromigration and electroosmosis, in physically heterogeneous porous media and its impact on tracer distribution, reactant mixing and degradation efficiency. We perform experiments in a multidimensional setup, considering different types of heterogeneities, injected tracers and reactants, as well as background electrolyte pore water with different chemical composition and pH. We show that EK transport is significantly affected by the physical heterogeneities, due to the interaction between electrokinetic and hydraulic processes, and by the pore water chemistry that plays a key role on the magnitude and spatial distribution of electroosmotic fluxes. The latter affect the overall transport of charged and non-charged species, including the migration velocity of injected plumes, their spatial patterns, spreading and mixing with the background groundwater, and the extent of degradation and the spatio-temporal evolution of reactive zones in the heterogeneous porous media. Process-based numerical modeling allowed us to interpret the experimental observations and to disentangle the coupled effects of physical, chemical and electrostatic processes in the multidimensional, heterogeneous setups. Besides elucidating the mechanisms controlling electrokinetic transport, the results of this study have also important implications for practical field implementation of EK approaches in intrinsically heterogeneous subsurface systems.